ISLAMIC VALUES DALAM PENGAMBILAN KEPUTUSAN AKUNTANSI - Slamet Haryono (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
This research examines the influence of Islamic Values on the accounting judgement. Studies of religiosity are dominated by intrinsic and extrinsic religiosity approach. This study arranges religiosity instrument of Accounting and Auditing Standard for Islamic Financial Institutions. The of Islamic values in this study are derived trustworthiness, religious legitimacy, objectivity, professional competence and diligence, faith driven conduct, professional conduct and technical standards. The respondents were the employees of the Islamic financial institutions who has held accounting duties within the company. Data collection using the survey and used in data analysis total of 75 of 200 questionnaires distributed. The results showed that the religious legitimacy affect the accounting judgement significantly. Professional competence and diligence influence the accounting judgement significantly. Faith driven conductand professional conduct and technical standards affect the accounting judgement significantly. However, found no evidence showed of the influence of trustworthiness and objectivity on the accounting judgement signicantly.